2004
DOI: 10.1128/aem.70.12.6957-6962.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Novel Fusobacterium nucleatum Plasmid pKH9 and Evidence of an Addiction System

Abstract: Fusobacterium nucleatum is an important oral anaerobic pathogen involved in periodontal and systemic infections. Studies of the molecular mechanisms involved in fusobacterial virulence and adhesion have been limited by lack of systems for efficient genetic manipulation. Plasmids were isolated from eight strains of F. nucleatum. The smallest plasmid, pKH9 (4,975 bp), was characterized and used to create new vectors for fusobacterial genetic manipulation. DNA sequence analysis of pKH9 revealed an open reading fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…The A rea R equired for R eplication in a P lasmid O f F usobacterium (ARRPOF) motif ( Supplementary Figure S3 ) occurs in Fusobacterium nucleatum plasmid pKH9. Although this plasmid has a predicted rep (replication) gene, which presumably can replicate the plasmid, the plasmid can also replicate when the rep gene is deleted ( 56 ). A 1 Kb region that lacks predicted genes ( Supplementary Text ) was found to be sufficient for replication ( 56 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The A rea R equired for R eplication in a P lasmid O f F usobacterium (ARRPOF) motif ( Supplementary Figure S3 ) occurs in Fusobacterium nucleatum plasmid pKH9. Although this plasmid has a predicted rep (replication) gene, which presumably can replicate the plasmid, the plasmid can also replicate when the rep gene is deleted ( 56 ). A 1 Kb region that lacks predicted genes ( Supplementary Text ) was found to be sufficient for replication ( 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although this plasmid has a predicted rep (replication) gene, which presumably can replicate the plasmid, the plasmid can also replicate when the rep gene is deleted ( 56 ). A 1 Kb region that lacks predicted genes ( Supplementary Text ) was found to be sufficient for replication ( 56 ). This region was cut into two, and each sub-region individually failed to allow replication.…”
Section: Resultsmentioning
confidence: 99%
“…The two shuttle vectors developed for fusobacteria (58)(59)(60) and the sequencing and annotation of three strains representing subspecies F. nucleatum subsp. nucleatum, Fusobacterium nucleatum subsp.…”
Section: Figmentioning
confidence: 99%
“…Our finding that pFN1-like relaxases are more prevalent in F. nucleatum than detectable plasmids may in some instances reflect integration of plasmid elements into the bacterial chromosome. Additional hybridization studies using sequences from other fusobacterial plasmids such as pFN3 (Haake et al, 2000; Karpathy et al, 2007) and pKH9 (Bachrach et al, 2004) may indicate more extensive prevalence of plasmid-related sequences in this species.…”
Section: Discussionmentioning
confidence: 99%
“…The first report of plasmids from F. nucleatum indicated that plasmids or plasmid-related sequences were found in 18% of the oral isolates examined (McKay et al, 1995). Plasmids isolated from F. nucleatum are reported to range from 5 to 15 kb (Bachrach et al, 2004; Haake et al, 2000; McKay et al, 1995), which is insufficient to encode all the genes needed for conjugation of self-transmissible plasmids. However, sequence analyses of several F. nucleatum plasmids revealed homologues of plasmid relaxases suggesting that the plasmids may be mobilizable with conjugative functions provided in trans (Haake et al, 2000; Karpathy et al, 2007).…”
Section: Introductionmentioning
confidence: 99%